Meningkatkan Aktivitas Dan Hasil Belajar Siswa Muatan Ppkn Tema 8 Menggunakan Model Bauntung Dan Video Pembelajaran Pada Siswa Kelas V SDN Kelayan Timur 5 - Muhammad Hendra; Sulaiman (Jurnal Pendidikan Sosial Dan Konseling, 2023)
The learning problem is the low student activity and learning outcomes in Civics learning. What is caused by learning is still one-way, less interesting, fun, and less meaningful for students. Efforts to overcome this by means of the BAUNTUNG model. The purpose of this research is to describe teacher activities, analyze student activities and improve learning outcomes. This study used Classroom Action Research (CAR) which was carried out in four meetings. The subjects of this study were fifth grade students at SDN Kelayan Timur 5 with a total of 25 students. This study uses qualitative and quantitative data obtained through observing teacher activities, observing student activities and written tests in groups and individually. The results of this study indicate that teacher activities were carried out with the criteria of "Very Good" at meeting 4. Student activities at meetings 3 and 4 achieved the criteria "Almost All Active". The classical completeness of student learning outcomes increased at the meeting of 4 cognitive aspects 100%, 100% affective and 100% psychomotor. Based on these findings, it can be concluded that the BAUNTUNG learning model can increase student learning activities and outcomes in PPKn Theme 8 Grade V SDN Kelayan Timur 5 content. It is recommended to use this model as an alternative in increasing student activity and learning outcomes. Keyword: Learning Activities, Learning Outcomes, BAUNTUNG.